Three rings a tale of exile, narrative, and fate - Mendelsohn, Daniel Adam 1960- (University of Virginia Press, 2020)
"This book explores the themes of exile and wandering, homecoming and fated closures in literature-but also in real life and history-by invoking Homer's Odyssey. Focusing on crucial moments in the lives and careers of three scholar/writers-Erich Auerbach, François Fénelon, and W.G. Sebald-all of whom were inspired by Homer's epic, Three Rings uses "ring composition" (Homer's dominant narrative technique) to tell the stories of the three writers' lives"--
Entstand aus dem Vortrag "A Digression: Narrative Afterlives of The Odyssey", der im Rahmen der Page-Barbour lectures 2019 an der University of Virginia stattfand
Keywords: Auerbach, Erich / 1892-1957 / Criticism and interpretation; Fénelon, François de Salignac de La Mothe- / 1651-1715 / Criticism and interpretation; Sebald, W. G. / (Winfried Georg) / 1944-2001 / Criticism and interpretation; Homer / Odyssey; Homer / Influence; Mendelsohn, Daniel Adam / 1960-; Auerbach, Erich / 1892-1957; Fénelon, François de Salignac de La Mothe- / 1651-1715; Homer; Sebald, W. G. / (Winfried Georg) / 1944-2001; Sebald, W. G. -- 1944-2001; Auerbach, Erich -- 1892-1957; Fénelon, François de Salignac de La Mothe -- 1651-1715; Odyssey (Homer); Literature, Modern / Classical influences; European literature / Classical influences; Critics / United States / Biography; Critics; Rezeption; Antike; United States